Dynamics of Netizen Criticism of the Performance of the Indonesian National Team in the Instagram Comment Column @Timnas Indonesia - Dani, Ahmad; Sakrim, Sakrim (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study discusses the directive command of netizen criticism of the performance of the Indonesian national team in the Instagram comment column @timnas indonesia. Pragmatics as the basis in this study on the form of directive command actions. The purpose of this study is to reveal the form of directive command of a comment on the Instagram platform of the @Timnasindonesia account. The type of research used is qualitative descriptive, documentation is carried out by screenshotting comments containing elements of directive commands on certain posts, then analyzed to find anything related to the directive command as a criticism written in the comment column. The results of the study showed that there were several netizen criticisms on the Instagram platform of the @Timnasindonesia account containing elements of directive forms, which can be found in the comments in a post, thus producing the data needed for research. The findings of the study are expected to provide a future overview of language science, especially pragmatics and can provide a deeper understanding of the form of directives on the Instagram platform.